Kdr genotyping (V1016I, F1534C) of the Nav channel of Aedes aegypti (L.) mosquito populations in Harris County (Houston), Texas, USA, after Permanone 31-66 field tests and its influence on probability of survival. - Jonathan R Hernandez; Michael Longnecker; Chris L Fredregill; Mustapha Debboun; Patricia V Pietrantonio (PLoS Neglected Tropical Diseases)
Aedes aegypti (L.) is an important mosquito vector of emerging arboviruses such as Zika, dengue, yellow fever, and chikungunya. To quell potential disease outbreaks, its populations are controlled by applying pyrethroid insecticides, which selection pressure may lead to the development of insecticide resistance. Target site insensitivity to pyrethroids caused by non-synonymous knockdown resistance (kdr) mutations in the voltage-gated sodium (NaV) channel is a predominant mechanism of resistance in mosquitoes. To evaluate the potential impact of pyrethroid resistance on vector control, Ae. aegypti eggs were collected from eight mosquito control operational areas in Harris County, Texas, and emerged females were treated in field tests at four different distances from the pyrethroid Permanone 31-66 source. The females were genotyped by melting curve analyses to detect two kdr mutations (V1016I and F1534C) in the NaV channel. Harris County females had higher survivorship rates at each distance than the pyrethroid-susceptible Orlando strain females. Survivorship increased with distance from the pyrethroid source, with 39% of field-collected mosquitoes surviving at 7.62 m and 82.3% at 22.86 m from the treatment source. Both the V1016I and F1534C pyrethroid resistant genotypes were widely distributed and at high frequency, with 77% of the females being double homozygous resistant (II/CC), this being the first report of kdr mutations in Ae. aegypti in Harris County. Analysis of the probability of survival for each mutation site independently indicated that the CC genotype had similar probability of survival as the FC heterozygous, while the II genotype had higher survival than both the VI and VV, that did not differ. The double homozygous resistant genotype (II/CC) had the highest probability of survival. A linear model estimated probability of survival for areas and genotypes. The high frequency and widespread distribution of double-homozygote pyrethroid-resistant Ae. aegypti may jeopardize disease vector control efforts in Harris County.